Isolation and partial characterization of the adduct formed by 13-hydroxyellipticine with deoxyguanosine in DNA - Moserova, Michaela; Kotrbova, Vera; Rupertova, Martina; Naiman, Karel; Hudecek, Jiri; Hodek, Petr; Frei, Eva; Stiborova, Marie (Neuro endocrinology letters, 2008)
OBJECTIVES: Ellipticine is a potent antineoplastic agent exhibiting multiple mechanisms of its action. Recently, we have found that 13-hydroxyellipticine, formed from ellipticine as the predominant metabolite in human livers, is bound to deoxyguanosine in DNA, generating the major DNA adduct in vivo and in vitro. The development of the methods suitable for the preparation of this adduct in the amounts sufficient for identification of its structure and those for its isolation and partial characterization is the aim of this study. METHODS: High performance liquid chromatography (HPLC) was employed for separation of 13-hydroxyellipticine-mediated deoxyguanosine adduct. The 32P-postlabeling technique was utilized to detect this adduct in DNA. RESULTS: The formation of the 13-hydroxyellipticine-derived deoxyguanosine adduct in DNA in vitro was increased under the alkaline pH of the incubations and by the formation of the sulfate and acetate conjugates of 13-hydroxyellipticine generated by reactions with 3'-phosphoadenosine-5'-phosphosulfate (PAPS) or acetyl-coenzyme A (acetyl-CoA) catalyzed by human sulfotransferases (SULTs) 1A1 and 1A2 and N,O-acetyltransferases (NATs) 1 and 2. The HPLC method suitable for separation the 13-hydroxyellipticine-derived deoxyguanosine adduct from other reactants, deoxyguanosine and 13-hydroxyellipticine, was developed. The structure of this adduct is proposed to correspond to the product formed from ellipticine-13-ylium with the exocyclic 2-NH2 group of guanine in DNA. CONCLUSIONS: The data are the first report on HPLC isolation of the deoxyguanosine adduct formed by 13-hydroxyellipticine in DNA and its partial characterization.
Keywords: izoenzymy; adukty DNA; Acetyl Coenzyme A; Arylsulfotransferase; acetylkoenzym A; Autoradiography; indikátory a reagencie; autoradiografie; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; deoxyguanosin; Phosphoadenosine Phosphosulfate; DNA Adducts; Isoenzymes; arylamin-N-acetyltransferasa; fosfoadenosinfosfosulfát; Indicators and Reagents; Catalysis; DNA; Arylamine N-Acetyltransferase; Ellipticines; elipticiny; arylsulfotransferasa; Deoxyguanosine; katalýza